2003
DOI: 10.1046/j.1463-1318.2003.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT and MRI in the pre‐operative staging of rectal adenocarcinoma and prediction of circumferential resection margin involvement by MRI

Abstract: These results suggest significant differences between accurate pre-operative "T" staging by CT and MRI for rectal cancer. MRI has the potential however, to accurately assess mesorectal envelope invasion. Further analysis is required to assess whether MRI can be used as the sole modality in pre-operative staging of rectal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 20 publications
1
68
0
6
Order By: Relevance
“…This high accuracy rate has not been achieved by EUS, conventional CT or multidetector CT (32). In a comparative study by Mathur et al (42), CT correctly staged patients with T1/T2 rectal cancers more often than MRI (77% vs. 43%, respectively, P = 0.226), and these patients were overstaged more often by MRI compared to CT (54% vs. 23%, respectively, P = 0.226). In this study, the majority of patients with T3 tumors were correctly staged by MRI compared to CT (76% vs. 41%, respectively, P = 0.08), and more T3 disease was understaged by CT than MRI (54% vs. 18%, respectively, P = 0.032).…”
Section: Discussionmentioning
confidence: 96%
“…This high accuracy rate has not been achieved by EUS, conventional CT or multidetector CT (32). In a comparative study by Mathur et al (42), CT correctly staged patients with T1/T2 rectal cancers more often than MRI (77% vs. 43%, respectively, P = 0.226), and these patients were overstaged more often by MRI compared to CT (54% vs. 23%, respectively, P = 0.226). In this study, the majority of patients with T3 tumors were correctly staged by MRI compared to CT (76% vs. 41%, respectively, P = 0.08), and more T3 disease was understaged by CT than MRI (54% vs. 18%, respectively, P = 0.032).…”
Section: Discussionmentioning
confidence: 96%
“…The lack of positive CRM in this series may be a reflection of the small sample size in this trial or because of initial clinical over-staging particularly as MRI was not routinely used preoperatively. It has been recognised that a degree of inaccuracy in clinical staging can occur comparing the reporting of preoperative radiological imaging to pathological staging [23]. Another possible explanation is that an element of down-staging occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The role of circumferential resection margin as an important prognostic indicator of local recurrence is evident and several MRI studies have shown a high accuracy in this regard [12,25,26] . BeetsTan et al [12] used contrast-enhanced thin section MRI on a 1.5 tesla scanner with a quadrature phased-array spine coil and reported that the depth of transmural tumor invasion and mesorectal fascia involvement were predicted correctly in 83% and 100% of their patients, respectively.…”
Section: C B Amentioning
confidence: 99%